Determinasi Kemudahan Akses Informasi bagi Keputusan Investasi Gen Z - Wirawan Widjanarko; Hadita Hadita; Farhan Saputra; Y.A. Didik Cahyanto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This research aims to determine the ease of access to information for Gen Z investment decisions. This research uses descriptive qualitative methods and literature reviews. Qualitative research is also intended to understand how someone thinks, acts and obtains information from a phenomenon. The data used is narrative and qualitative, obtained from previous research documents and obtained novelty in this research. Data analysis used in this qualitative research is the Miles and Huberman interactive model. This qualitative research is exploratory in nature. The type of data used is secondary data. The focus of this research is ease of access to information. The results of this research are: 1) That the use of technology and digital platforms for easy access to information for Gen Z in investing is quite good, where Gen Z uses social media as a platform to gain knowledge regarding good investment instruments, a means of discussion and exchanging views between Gen investors. Z, then the platform that provides easy access to information for Gen Z in investing is quite varied, from the Bibit, DANAeMAS, Ajaib, Tokopedia to Shopee applications, apart from that, payments made can also utilize digital banking and digital wallet payments; 2) Generation Z or Gen Z chooses forms of investment instruments with (high risk high return) high risk high returns such as stocks and cryptocurrencies, while generation Y and generation X choose forms of investment instruments with (low risk low return) low risk low returns such as jewelry gold and mutual funds; and 3) The amount of investment made by Gen Z varies, where in the July 2023 period it was IDR 7,658,506, while in the August 2023 period it was IDR 7,645,956.